Financial Performance Analysis at PT. Pegadaian (Persero) Period 2018-2022 - Helmi panus Panus; Agus Wahyudi; Ludgardis Deliman; Yohanes Paulus Hanny Wadhi (The Es Accounting And Finance, 2023)
This study aims to determine the financial performance of PT. Pawnshop (Persero). This type of research is descriptive quantitative, namely explaining financial ratios consisting of Liquidity Ratios, Solvency Ratios, Activity Ratios, and Profitability Ratios. With observations over the last five years (2018-2022), through documentation in the form of financial reports obtained from PT. Pawnshop. The results showed that the financial performance at PT. Pegadaian (Persero) for the last five years has been in an unstable condition, experiencing increases and decreases. Measurement of financial performance using the liquidity ratio which consists of the current ratio, quick ratio and cash ratio. Subjected to different fluctuations. With the average obtained, the current ratio is 182%, the quick ratio is 180% and the cash ratio is 2%. Solvability ratios consisting of a debit to asset ratio and a debit to equity ratio show very good financial performance. With the average obtained, for a debit to asset ratio of 62% and a debit to equity ratio of 168%. Profitability ratios consisting of NPM (Net Profit Margin), return on assets and return on equity show that financial performance tends to experience instability, which means there are increases and decreases. With an average of each, a net profit margin of 75%, return on assets of 4% and return on equity of 58%. The activity ratio consists of total asset turnover with an average of 29 times indicating very good financial performance. While fixed asset turnover with an average of 1.85 times which indicates poor financial performance.